Sociabilidades: deslocamentos em fluxos nos usos de tecnologias digitais por alunos de duas escolas públicas de São Luís (MA) - Santos, Maria José dos (2016)
We studied the relationships in this research between technologies and news forms of sociabilities understood uses of digital technologies (TDs) by fourteen students of two State public schools of the city of São Luis – MA. We assumed that the students to use News Information and Communication Technologies (TIC) in school space produce digital sociabilities that can causes shifts socialization process. We have as main objective understand assigned meaning for public school students in the terms of information and communication technologies in the school space. We use as main reference unit interviews conducted and interpreted by means of the methodology of the Comprehensive Interview. We take the word while the subject concrete act as analysis unit the richness of meanings that word has. The meanings revealed in the process of listening and analysis of date confirmed the initial assumption developed in course of the construction of the search object. We tried this study contribute to the research on technologies and social arrangements and relationship school students and digital technologies in the context of the school and their daily lives.